LIQUIDITY, PROFITABILITY, AND SOLVENCY: COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE - Tri Purwanti; Sry Wahyuni Hasan; M.U. Falah; Sri Hermuningsih (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the comparison of financial performance of PT Timah Tbk with PT Golden Energy Mines Tbk in terms of liquidity, profitability and solvency ratios. This type of research data is secondary data. Data collection techniques with literature and documentation. Data analysis used in liquidity ratio analysis consists of Current Ratio (CR), and Quick Ratio (QR), profitability consisting of Return on Asset (ROA) and Return On Equity (ROE), and solvency ratios namely Total Debt To Equity Ratio and Total Debt To Total Asset Ratio. The results showed that PT Timah has more ability to pay its short-term debt, more ability to pay its short-term debt that has been reduced by inventory when compared to PT Golden Energy Mines Tbk. PT Golden Energy Mines Tbk has more ability to obtain net profit after tax from total assets, more ability to obtain net profit after tax from total equity when compared to PT Timah Tbk. PT Timah Tbk has a lower level of debt risk and a lower level of debt risk when compared to PT Golden Energy Mines Tbk.